(untitled) (Revista científica Olimpia, 2020)
The objective of this work is to investigate and theorize about a set of theoretical-critical reflections in the area of ​​recreation and public policies developed in some Latin American countries. It is approached from a transdisciplinary and complex epistemological view, methodologically oriented from the Gadamerian documentary and hermeneutical research. The importance is expressed in unveiling the development of policies in the recreational area and rethinking public policies from a perspective that marks distance with the capitalist logic instituted in some Latin American countries. The challenge is to propose a decisive differentiating element with capitalism and thus, to go through a stage of construction of a different recreation idea, is to move towards a recovery of the act of freedom; assumed from being able to make a pleasant, fun, formative recreation and less tending towards consumerism that allows establishing new bases for living well for citizens. Among the most outstanding findings we have the possibility of knowing, deconstructing and re-creating the discourse of recreational praxis from some premises: knowledge production, innovation and creativity, criticism as a place, recreation for the cultivation of democracy, generation of collective values, Recreation a forum to deliberate, wisdom, recreation and technological development, management model, utopian construction.